2016
DOI: 10.1002/navi.140
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Vehicle Dynamic Model-Based Navigation for Small UAVs

Abstract: This paper presents a novel approach to autonomous navigation for small UAVs, with no extra sensor added to the conventional INS/GNSS setup. The proposed method significantly increases the accuracy and reliability of autonomous navigation, especially for small UAVs with low‐cost IMUs. This improvement is of special interest in the case of GNSS outages, where inertial coasting drifts very quickly. In the proposed architecture, the VDM provides the estimate of position, velocity, and attitude, which is updated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…GPS with INS aiding has been applied, along with other sensors, to multiple vehicular and UAV applications and has been shown to provide position estimates where GPS is intermittently unavailable. Khagani et al have demonstrated that fusing GPS/INS with a vehicle dynamic model leads to major improvements in navigation accuracy in periods of GPS outages . Klein et al rely on a navigation solution and use pseudorange measurements as aiding to navigate periods of GPS outages.…”
Section: Related Workmentioning
confidence: 99%
“…GPS with INS aiding has been applied, along with other sensors, to multiple vehicular and UAV applications and has been shown to provide position estimates where GPS is intermittently unavailable. Khagani et al have demonstrated that fusing GPS/INS with a vehicle dynamic model leads to major improvements in navigation accuracy in periods of GPS outages . Klein et al rely on a navigation solution and use pseudorange measurements as aiding to navigate periods of GPS outages.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, each UAV is assumed to be loaded with the same magnetic anomaly map. Meanwhile, each UAV is assumed to be able to measure or estimate its velocity and yaw rate through some methods, such as using Vehicle Dynamic Model (VDM) presented in [37] or Visual Odometry presented in [38,39]. No additional information is used for UAV navigation in this study.…”
Section: Problem Statementmentioning
confidence: 99%
“…In , the authors apply the VDM approach using a completely different perspective. They use the IMU as observation not as the main process model, while the VDM is used as the main process model, so any additional data available from IMU or GNSS act as observations for the VDM model.…”
Section: Related Workmentioning
confidence: 99%